MENENTUKAN KEDALAMAN DAN KETEBALAN AKUIFER DENGAN METODE LOGGING TAHANAN JENIS PADA WAKTU PENGEBORAN AIR TANAH - Sri M. Yuningsih (JURNAL SUMBER DAYA AIR, 2009)
The aim of this resistivity logging measurement is to decide the stratification of rock and distribution ofaquifer based on the resistivity value. The objective of the well logging is to determine the depth and thicknessof aquifer for well construction, in order to decide the position of screen in the aquifers .Interpretation resultsof the resistivity logging of aquifer of sand and sandy tuff vary between 20 40 ohm-m and 60 115 ohm-m forbreccia. Groundwater in the Ciparay and Cibodas areas is predicted in the depth of 42 66 m and 75 108 m,consisting of intercalation of young volcanic fan and Bandung lake deposit. The aquifer in Dago area is lessthan 100 m deep representing young volcanic deposit including the Cibeureum Formation, whereas aquiferswith a depth of more than 100 m comprise volcanic deposit, including the Cikapundung Formation. It isrecommended to extract groundwater from more than 50 m deep, in order to prevent influence to phreaticaquifer as excavated well. The minimum kind of well logging for groundwater drilling should consist ofresistivity, self-potential and gamma ray logging.